Eletrodos de grafite modificados com politiramina : preparação e incorporação de metais para geração de hidrogênio - Castro, Cláudio Márcio de (2007)
This work reports modification of the surface of graphite electrodes by electrochemical polymerization of tyramine. These modified electrodes were used to nickel or platinum incorporation and hydrogen evolution. Tyramine electrooxidation, in acid and basic media, yielded polymeric films onto graphite surface. In ferrocyanide/ferricyanide solution, the electrodes modified in acid medium showed higher electron transfer efficiency. Impedance studies indicated higher charge transfer resistance to electrodes modified with Ptyr prepared in basic pH. Scanning electron microscopy showed that the formed films present different morphology for the several pH values studied. Interferometry and scanning electron microscopy analysis showed higher coverage to films formed in acid medium. Polymers produced in more alkaline medium present growth self-limited. Nickel or platinum was incorporated in the films through immersion of the modified electrodes in solution of potassium hexafluoronickelate and potassium tetrachloroplatinate, followed of electrochemical reduction of the ion. The electrocatalytic activity of the modified electrodes with the metals incorporated was tested for hydrogen evolution reaction. The amount of nickel and platinum mass incorporated as well as the current density of hydrogen evolution reaction was higher in electrodes modified with polytyramine produced in acid medium.